Development of fluorescence based probes for disease imaging - Tetyana, Phumlani (My University, 2018)
Microscopy detection has once been the gold standard in the detection of infectious diseases such as tuberculosis and cancer, and therefore improvements in the detection procedure could further enhance sensitivity and restore its use. Fluorescent probes for microscopy detection have been synthesized using organic dyes which have numerous limitations, such as a narrow absorption spectra and a broad emission spectra to name but a few, that impact negatively on assay sensitivity. Use of semiconducting nanomaterials in the design of fluorescent probes for disease detection eliminates the aforementioned limitations and enhances the sensitivity of detection, and also allows for the detection of multiple disease analytes further improving the scope of detection which eliminates misdiagnosis. Moreover, commercially available nanomaterials are synthesized from toxic elements such as cadmium, lead and mercury; using an organometallic synthesis route which further yields nanomaterials not suitable for bio applications. This study is based on the aqueous synthesis of semiconducting nanomaterials for use as fluorophores in the development of fluorescent probes for imaging of cellular materials. Copper and Cobalt sulfide nanomaterials were of interest in our study. They were synthesized via an aqueous synthesis method, using four different capping ligands, namely; glutathione, thioglycolic acid, 18-crown-6 and L-carnosine. Reactions were performed at either 50 and 95 ˚C, using deionized water as a solvent. The optical and structural properties of as-synthesized nanoparticles (NPs) were investigated using UV/Vis absorption spectroscopy (UV-Vis), Photoluminescence spectroscopy (PL), Transmission Electron Microscope (TEM), X-Ray Diffraction (XRD) spectroscopy and Fourier Transform Infrared Spectroscopy (FT-IR). The cytotoxic properties of as-synthesized NPs were investigated using the 3-[4,5dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide tetrazolium assay (MTS). Fluorescent probes were constructed by conjugating hypoxia inducible factor-1α (HIF-1α) and the Phosphohistone H2A.X (Phospho H2A.X) monoclonal antibodies to as-synthesized NPs using carbodiimide chemistry. The fluorescent probes were used to target HIF-1α and Phospho H2A.X proteins produced in mammalian cells (Human Embryonic Kidney (Hek293) and HeLa cells) undergoing apoptosis, in vitro. iii The optical properties of as-synthesized NPs depicted absorption spectra that are blue shifted from their bulk counterparts, signifying the formation of small nanoparticles. This is due to quantum size effects. Copper sulfide nanoparticles depicted emission peaks that are red shifted from their respective absorption spectra while cobalt sulfide nanoparticles revealed red shifted emission spectra. TEM images revealed the formation of various morphologies, including spheres, hexagons and rods, in response to the use of different capping ligands, synthesis temperatures and sulfur sources. The size of nanoparticles was greatly influenced by the reaction temperature, with small nanoparticles formed at 50 ˚C while bigger particles were formed at 95 ˚C. The XRD revealed the formation of mixed phases when the temperature of the reaction was set at 50 ˚C. At 95 ˚C, single phases were formed and the reactions were seen to be complete as no evidence of non-reacted material was observed. The interaction of the capping ligands with NPs was confirmed via FT-IR, with various capping ligands employing different functional groups to attach to the surface of NPs, which were not affected by reaction temperature or sulfur source employed. The cytotoxicity of as-synthesized NPs was investigated using an MTS assay. Copper sulfide NPs were seen to be non-toxic at concentrations below 6µg/ml, with a dose dependant decrease in cell viability observed throughout. However, for CuS NPs synthesized at 50 ˚C using SDEDTC, a decline is observed when the concentration of nanoparticles exceeds 3.125 µg/ml. CoxSy NPs were found to be non-toxic to MT-4 cells, with cell viability maintained above 80% even at the highest concentration tested. Fluorescent probes were developed by conjugating antibodies to CuxSy NPs for imaging purposes. A slight shift to higher wavelength was observed in the absorption spectra of CuxSy NPs after the conjugation step, signifying the presence of the antibodies on the surface of nanoparticles. When tested in vitro using cells treated with CoCl2 and doxorubicin, the fluorescent probes were internalised by the cells, but their fluorescence intensity was low when compared to cells treated with nonconjugated nanoparticles. These results demonstrate the feasibility of utilising these nanoparticles in the development of fluorescent probes for biological imaging applications in vitro, with further optimisation.
A thesis submitted to the Faculty of Science, School of Chemistry at University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2018
Keywords: Fluorescent antibody technique